Natural lighting of road pre-tunnels: A methodology to assess the luminance on the pavement – Part II. (March 2018) - Cantisani, Giuseppe; D'Andrea, Antonio; Moretti, Laura
Abstract: This two-part paper presents a comprehensive methodology for lighting calculation of a road pre-tunnel. The adequate lighting of road tunnels, especially in their entrance zone during the day-time hours, is a very important factor to maintain road safety and to ensure a good level of service. These targets are commonly achieved by means of artificial lighting systems. In some cases, nevertheless, it could be preferable to build a pre-tunnel, which reduces and controls the natural lighting contribution in the threshold zone of the tunnel. The structure, in fact, filters the natural light and permits to achieve the required luminance levels on the road pavement, so ensuring the correct visibility to the drivers. Analytical models were developed in the first part of the paper to describe the sky illumination of a clear but not terse sky, which is typical in large cities and industrial areas, and to evaluate the consequences related to the construction of a pre-tunnel lighting (PTL). This second part presents the validation procedures adopted to verify the proposed models. Particularly, a luxmeter photo-radiometer has been used for validating the clear not terse sky model and several PTL scale models were used to validate the methodology proposed to assess the pavement luminance. The geometry of the PTL, its alignment and materials have been varied to obtain several results under various meteorological and climatic conditions. The results obtained from the experimental research program showed that the proposed models, inherent both the sky luminance and the illuminance on the road, ensure a good approximation respect to the real measures performed. In particular, for the sky luminance, the proposed theoretical distribution implies an average deviation respect to the experimental data equal to 5%. The calculated illuminance under the PTL differs on average from the measured values for −1.26%.